(3fGXQI GdYjf aj TQM fGXQI GdYjfs - (3CMeO Hf YeQ Hf Ydj Hf gdGd GdeGdcjs; (3eMehO Hf YHO GdQMef Hf CMeO Hf eMeO, CHh GdKfGA, TeS GdOjf GdCUagGfj, Ch GdCUHgGfj ,J (B749 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa fhY GdEfSGf HGdefWb hGdHjGf hHYO abO GJab GdaVdGA Ydi Cf GdYde CaVd GdSYGOGJ hCced GdOQLGJ s
(3BNQgG (B:s
(3dCf bhdfG Efg PgH eMGd (B,(3Gdbhd HCfg LSe UOb (B( (3? (B) (3hgfG GfJgi eG bUOfGg ef GdEedGA s
(3aQZ GdeUfa ef JCdjag SfI (B779s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B173 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B6 - (3U (B409s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs